Endogeneity, Heterogeneity and Determinants of Inefficiencies in Crop-Producing Farmers: Evidences from Central Highlands of Ethiopia - Oumer Beriso (Ethiopian Journal of Science and Sustainable Development)
Agricultural sector is crucial for Ethiopia's overall economic growth and has notable spillover effects. Hence, it is essential to conduct recurrent analysis of production performance, investigating efficiency level and inefficiency differentials, which are key indicators of productivity growth and informative for policymakers. This paper estimated transient and persistent inefficiencies distinguished from farm-heterogeneity and endogeneity for Ethiopian grain crop-producing farmers for the period of 2004 – 2015. The study used Mundlak-adjusted random effect – four error component stochastic frontier model by extending earlier version of the model to distinguish endogeneity and farm-heterogeneity from time-invariant inefficiency and to explain inefficiencies. The adjusted model was then estimated using multi-step estimation. The mean estimates of   persistent, transient and overall efficiencies were 79, 73 and 58%, respectively. Result from inefficiency effect model revealed sex, family-size, number of plots, owing-oxen, soil-fertility and rainfall influenced transient inefficiency negatively; while, age, education, and temperature variation had positive effect. Persistent inefficiency was influenced negatively by owing-oxen, soil-fertility, farm-size, population pressure, rainfall, and market proximity; whereas, age and education affected it positively. Generally, the overall technical efficiency is low, mainly due to the transient part. In conclusion, the findings are vital to initiate government policy options to reduce inefficiency, focusing on factors affecting the long-run and short-run inefficiencies distinctly. The low level of efficiency can be addressed by facilitating farmers’ access to more arable-land and modern farming tools and machinery, creating targeted support programs for female farmers, improving technologies that promote soil-fertility and reduce weather adverse effects in central highlands of Ethiopia.